Third trimester of pregnancy: Carpal tunnel syndrome, anxiety and depression - Tupković Emir; Nišić Mediha; Salihović Semiha; Kunić Suljo (Sanamed, 2013)
This study measured the frequency of carpal tunnel syndrome (CTS) and the levels of anxiety and depression in the third trimester of healthy pregnant women having regular prenatal visits. The study was performed at the Department of Neurophysiology Health Centre Tuzla in the period of January through April 2006. The group consisted of 40 pregnant women in the third trimester of pregnancy, age range of 25.6 ± 4.9 years. The control group consisted of healthy women, ages 31.1 ± 4.4 years. The electrophysiological parameters n. medians, the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were measured. The diagnosis of CTS is neurophysiologically confirmed in 12 pregnant women (30%) and 75% showed clinical signs and symptoms of disease. Pain was measured by subjective pain scale ranked from 0 (absence of pain) to 10 (severe pain). The mean value of BAI in control group was 8.6 ± 6.5, while in the group of pregnant women was 12.9 ± 6.9, which was significantly higher (p = 0.011). The mean value of BDI in control group was 4.2 ±4.4 and in the group of pregnant women was 8.7 ±5.9. which was significantly higher (p = 0.0008), The mean value of BAI in the group of women with CTS was 12.25 ± 6.7 which was not significantly higher than the compared to the control group (p = 0.113). The mean value of BDI in the group of pregnant women with CTS was 7.9 ± 6.4,which was significantly higher when compared to the control group (p = 0.037). The subjective assessment of pain in the group of women with CTS was 2.4 ±2.1. There was a slight correlation between pain intensity and degree of BAI (r = 0.289) and a negative correlation with the level of depression (r = - 0.297). The conclusion is that pregnant women with normal risk should make an extra effort in the treatment of unpleasant conditions such as CTS, anxiety and depression, which may impair the quality of life and have physical and psychological side effects on the future mother.